THE EFFECT OF WALKING EXERCISE ON FATIQUE IN CANCER PATIENTS WHO WALK IN CHEMOTHERAPY AT RSUP Dr. M.DJAMIL PADANG - Weny Amelia; Mira Andika (Nurse and Health: Jurnal Keperawatan, 2019)
Background: Cancer is a disease characterized by abnormal and uncontrolled growth of abnormal cells that can damage the surrounding tissue and can metastasize. Chemotherapy is one of the modalities that is often used by cancer patients. The problem that often arises in cancer patients undergoing chemotherapy is fatigue. Walking exercise is a nonpharmacological strategy that can improve fatigue scores.Objective: The purpose of this study was to determine the effect of giving walking exercise on fatigue in cancer patients undergoing chemotherapy at RSUP Dr. M. Djamil Padang.Method: The research design uses quasi-experimental in the form of a pretest-posttest with control group approach. The sampling technique was purposive sampling with a large sample of 15 intervention groups and 15 control groups. Fatique scores were assessed using the Piper Fatique Scale (PFS). Statistical tests using Paired T-Test.Result: The result is a significant effect of walking exercise on fatigue in cancer patients undergoing chemotherapy (p value = 0,000; α = 0.05).Conclusion: The results of this study recommend walking exercise as an independent nursing intervention to improve physical scores in cancer patients undergoing chemotherapy. Key words: Fatique, cancer, chemotherapy, walking exercise.